Chronic Recurrent Multifocal Osteomyelitis - A Case Report - Cecil K Eldhose; Mohammed Tavfiq; J K Giriraj Harshavardhan; Sundar Suriyakumar; C Sitsabesan (Journal of Orthopaedic Case Reports)
Introduction: Chronic recurrent multifocal osteomyelitis (CRMO) is a benign, noninfectious, self-limiting inflammatory bone disease that predominantly affects children and adolescents, characterized by multiple, recurrent osteolytic and sclerotic lesions typically involving the metaphysis of long tubular bones, clavicle, spine, and pelvic. The clavicle, particularly its medial end, is the most common and characteristic site affected. Case Report: A 13-year-old boy presented with a 5-month history of acute gradually progressive, dull aching pain over the bilateral hip radiating to the thigh, knee, and ankle. Myeloproliferative disorders were ruled out with a bone marrow biopsy. Magnetic resonance imaging pelvis with hip, thigh, and clavicle screening showed altered signal intensities involving the bilateral acetabulum, pubic bones, iliac bone, right femur, bilateral tibia, and clavicle, along with diffuse periosteal thickening involving the left iliac wing. After ruling out all possible differential diagnosis and discussion in a multidisciplinary team, a final diagnosis of CRMO was made. The patient was started on Inj. Pamidronate and responded well to treatment. Conclusion: CRMO is a rare benign bone lesion with diverse clinical presentation and lack of specific clinical, laboratory, or pathological features, which leads to misdiagnosis or delayed diagnosis. A high index of suspicion and characteristic radiological involvement of the clavicle may help to clinch the diagnosis. Familiarity with this condition greatly increases the likelihood of early diagnosis and appropriate management.